SIMULASI PENGGUNAAN DIFFUSER PADA TURBIN ANGIN SUMBU HORISONTAL UNTUK KENAIKAN DAYA - Atmadi, Sulistyo; Fitroh, Ahmad Jamaludin (BRIN Publishing, 2011)
One technique to improve the power output of a wind turbine is by implementing a diffuser, which is called the diffuser augmented wind turbine (DAWT). The area ratio between the inlet and outlet of the diffuser increases the flow rate inside the diffuser which in effect produces higher output power. In this research, a 2 meters rotor diameter was used. Diffuser diameter ratio variation of 2, 3, 4, and 5 were chosen which provides inlet diameter of 4, 6, 8, and 10 meter respectively. Power rotor coefficient is assumed to be constant of 0.30. Air speed distribution inside the diffuser is calculated using CFD method. The inlet speed to the diffuser is varied to give 4 different speeds. The wind angle at the inlet is also varied at 0º, 30º and 60º. The simulation result showed that at 0 degree angle, diffuser diameter ratio variation of 2, 3, 4, and 5 will increase the power output about 58, 622, 3169, and 11519 times respectively. It also showed that the increase in the output power for diameter diffuser ratio of 2 at 0º and 60º angle is 58 and 4 times respectively.